THE IMPORTANCE OF ACCENT, PHONICS, AND DIFFERENCES AMONG RUSSIAN, INDIAN, AND ENGLISH (Ustozlar uchun, 2026)
This article explores the significance of accent and phonics in effective communication and language learning, focusing on the phonetic and phonological differences among Russian, Indian, and English language systems. It examines how accents influence intelligibility and perception, highlighting challenges in pronunciation, vowel and consonant systems, and syllable stress patterns. The study also delves into the cultural and educational implications of accent differences, discussing strategies for learners and educators to bridge phonetic gaps.